Toward recovering and reconstructing andragogy - David Little (Adult Education Research Conference, 1994)
Emerging outlines for a reconstruction of andragogy are put forth. The situated activity stream of cultural psychology is initially explored and later connected to the Frankfurt stream of critical sociology with the intent to uncover a more robust construct of learning that holds potential for preserving the notion of a self-directed learner that is central to andragogy while at the same time superseding it with a conception of development within which learning is seen to occur as a culturally initiated, interpersonal process that is subsequently influenced through an intrapersonal process grounded in the somatics of the person.